2018
DOI: 10.1002/slct.201801076
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Tuning of Through‐Molecule Conductance in a Conjugated Calix[4]pyrrole

Abstract: A conformationally flexible calix [4]pyrrole possessing a conjugated electronic structure (an N-substituted oxoporphyrinogen (OxP) related to porphyrin) was used to investigate the influence of mechanical stretching on the single-molecule conductance of these molecules using the mechanicallycontrolled break junction (MCBJ) technique. The results show that the molecule can be immobilized in a single-molecule break junction configuration, giving rise to different behaviours.These include step-like features in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Further to historical efforts in organic synthesis and materials' fabrication, functional optimization of materials involving structural regulation at the atomic/molecular scales and nanometre scales has been widely investigated and has been accompanied by the corresponding developments in observational techniques and instrumentation on those length scales [37][38][39]. While it is widely appreciated that nanotechnology plays a central role in materials developments involving nanoscale structures, nanotechnology also provides substantial benefits in the development of nanoscale observation and fabrication techniques including deepening our understanding of novel phenomena on the nanoscale and their guiding physical principles [40][41][42][43]. The construction of functional materials from nanoscale units requires essential contributions from non-nanotechnology fields such as supramolecular chemistry with self-assembly/selforganization [44][45][46][47], materials fabrications [48][49][50], and biotechnology [51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Further to historical efforts in organic synthesis and materials' fabrication, functional optimization of materials involving structural regulation at the atomic/molecular scales and nanometre scales has been widely investigated and has been accompanied by the corresponding developments in observational techniques and instrumentation on those length scales [37][38][39]. While it is widely appreciated that nanotechnology plays a central role in materials developments involving nanoscale structures, nanotechnology also provides substantial benefits in the development of nanoscale observation and fabrication techniques including deepening our understanding of novel phenomena on the nanoscale and their guiding physical principles [40][41][42][43]. The construction of functional materials from nanoscale units requires essential contributions from non-nanotechnology fields such as supramolecular chemistry with self-assembly/selforganization [44][45][46][47], materials fabrications [48][49][50], and biotechnology [51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…The breakthrough for the development of organic devices is to develop smart devices able to replace all silicon semiconductor components. The trend is to learn with biological systems [79][80][81][82][83][84][85].…”
Section: Future Perspectivementioning
confidence: 99%
“…However, most of the mechanisms of biological systems still remain unknown. The focus has been centered in studying individual biological molecules [83,84].…”
Section: Future Perspectivementioning
confidence: 99%
“…In addition, metal‐porphyrin can be bridged by conjugative linkers and form conjugative metal‐porphyrin molecular dimer, but the corresponding spin transport properties have not been investigated. Moreover, in the process of mechanically controllable break junction (MCBJ) experiment, mechanical stretching and compressing can induce molecular dimer deformation ,. For example, Stefani et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stefani et al . demonstrated that the angle of conjugated calix[4]pyrrole molecule can be tuned by MCBJ technique, and the corresponding single molecule conductance exhibits a slower decay than measured for direct tunneling . So, in this paper, we have investigated the spin transport properties of a series of manganese diporphyrin (MnDP) by mechanical tuning of different dihedral angle by employing spin‐polarized density functional theory (DFT) combined with non‐equilibrium Green's function technique (NEGF).…”
Section: Introductionmentioning
confidence: 99%